2018
DOI: 10.1007/s11136-018-1942-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of the combination of sleep duration and sleep quality with quality of life in type 2 diabetes patients

Abstract: Specific disparities exist in the association of sleep quality with sleep duration and QOL in T2DM patients. Failures to take into account the effect of sleep quality when evaluating the impact of sleep on QOL significantly bias the results. It is important to integrate duration and quality of sleep as a composite sleep index when assessing sleep of patients with T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 38 publications
2
13
0
2
Order By: Relevance
“…It revealed that 66.4% people with T2D suffer from sleep symptoms and that their QoL, including HRQoL and overall activity impairment, was worse than those of respondents without symptoms. This finding correlates with the results of previous studies [6][7][8][9][10]27]. Also, this study revealed that waking up to go to the bathroom and daytime sleepiness are associated with worse QoL in people with T2D.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It revealed that 66.4% people with T2D suffer from sleep symptoms and that their QoL, including HRQoL and overall activity impairment, was worse than those of respondents without symptoms. This finding correlates with the results of previous studies [6][7][8][9][10]27]. Also, this study revealed that waking up to go to the bathroom and daytime sleepiness are associated with worse QoL in people with T2D.…”
Section: Discussionsupporting
confidence: 92%
“…These studies were based on the sleep disorder scores. These scores and sleep duration significantly correlate with QoL values in people with T2D [9,10]. Generally, these sleep disorder scores were meaning the summary of symptoms in previous studies.…”
Section: Introductionsupporting
confidence: 55%
“…These findings were supported by previous studies in adults. For example, Zeng et al [39] reported that long sleep duration was a risk factor for poor quality of life in patients with type 2 diabetes mellitus who reported poor sleep quality. In contrast, Chen et al [33] found the association between sleep duration and osteoporosis was most pronounced in postmenopausal women reported good sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…Given the effects of various factors, such as physical, emotional, and environmental factors, patients' sleep duration and sleep quality are substantially compromised. 16 Therefore, it is important for surgeons to realize that early postoperative interventions that can reduce anxiety and pain have an important impact on the rehabilitation of patients. Music therapy refers to the scientific and systematic application of the influence of music characteristics to aid in sleep, reduce anxiety associated with surgery, and help with local anesthesia.…”
Section: Discussionmentioning
confidence: 99%